2019
DOI: 10.1515/jcim-2018-0123
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Achillea wilhelmsii C. Koch capsules on symptom severity and quality of life in patients with irritable bowel syndrome: a randomized, placebo-controlled clinical trial

Abstract: Background Irritable bowel syndrome (IBS) is one of the most common digestive diseases. The aim of this clinical trial was to determine the effectiveness of Achillea wilhelmsii C. Koch on the symptom severity and quality of life (QOL) in patients with IBS. Methods The patients were randomized into two groups of 45 each. The QOL and symptom severity of the patients were evaluated at baseline and at completion of the treatments by means of IBS-QOL and IBS severity index. Results The mean severity of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Herein, we report the results of a comprehensive phytochemical investigation of A. wilhelmsii aerial part that led to the identification of 17 secondary metabolites (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), including the not yet described sequiterpenoids wilhelmsin (7) and wilhelmsolide (9). The structural elucidation for these new secondary metabolites, including peculiar structural features, was as well performed.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Herein, we report the results of a comprehensive phytochemical investigation of A. wilhelmsii aerial part that led to the identification of 17 secondary metabolites (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), including the not yet described sequiterpenoids wilhelmsin (7) and wilhelmsolide (9). The structural elucidation for these new secondary metabolites, including peculiar structural features, was as well performed.…”
Section: Introductionmentioning
confidence: 97%
“…This plant holds a remarkable place in traditional Persian medicine, with a particular indication for the treatment of pulmonary affections, and it is used by the local population for a variety of ailments [4]. Recent investigations have substantiated these traditional uses with a scientific approach and activity on irritable bowel syndrome and ulcerative colitis [5,6], and improvement of oxidative stress-related myocardial injury [7] have been demonstrated. Asgary et al [8] have reported a significant activity of A. wilhelmsii extracts in inducing a decrease in triglycerides and LDL-cholesterol levels after 2-4 months of the administration, a result supported by Khazneh et al [9] in a more recent investigation.…”
Section: Introductionmentioning
confidence: 99%